Ground Zero/Fresh Kills: Cataloguing Ruins, Garbage, and Memory (Altre Modernità, 2011)
The aim of this paper is to show how the rise and fall of the Twin Towers can be read in relation to the rise and fall of the Staten Island Fresh Kills landfill, how their destinies were entwined from the start, and how the immediate cultural response to the collapse of the former and the closing of the latter recurred to the form of catalogues of objects, words, and images. From this angle it will be possible to posit the events within a larger, if somewhat unusual, cultural frame encompassing the history of two different yet complementary symbols of New York up to 2001 (the WTC and Fresh Kills). From Don DeLillo’s Underworld (1997) and Falling Man (2007) through Holman, Steve Zeitlin e Joe Dobkin’s Crisis (2001-2002); from Art Spiegelman’s In the Shadows of No Tower (2004) to Artists Respond’s 9-11 (2002); from the New York Times to Bearing Witness to History, the 2003-2006 retrospective of the Smithsonian Museum, relevant collective or individual responses to the 2001 attacks took the form of a catalogue, a list, a vertical or horizontal juxtaposition of data, objects, and memories, evoking a suggestive parallel to the organizing principle of past relics collected in museums and garbage stratified in sanitary landfills.
Keywords: Ground Zero; Fresh Kills; cataloghi